From Screens to Skills: The Effect of the Cake App on Junior High Students' Vocabulary Achievement - Sitti Agustina; Nursenang; Anugrah Puspita Ayu Muhammad (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2025)
This study aims to determine whether there is a significant effect of using the Cake application on students' vocabulary achievement at the eighth grade of Junior High School 23 Kendari. The research employed a quasi-experimental design with two groups: an experimental class (VIII A) consisting of 25 students, which received treatment using the Cake application, and a control class (VIII B), which followed conventional teaching methods. A vocabulary test consisting of 45 items was used as the research instrument. The treatment was conducted over four weeks, with three sessions per week, each lasting approximately 30 minutes, combining in-class guided activities and independent practice at home. Data were analyzed using SPSS 20, including tests for normality, homogeneity, and an independent sample t-test. The results showed that the mean score of the experimental class increased significantly from the pre-test 47.88 to the post-test 81.88, and the gain score was 34.00. Meanwhile, the mean score of the control class was 44.08 and become 75.00 in the post-test. It creates 30.92 for the gain score. The independent samples t-test indicated a statistically significant difference between the groups (p = 0.021 < 0.05), indicating a significant difference in vocabulary achievement between the two groups. The null hypothesis (H0) was rejected and H1 is accepted. Therefore, these findings demonstrate that mobile-assisted vocabulary learning through the Cake application can effectively enhance students’ vocabulary acquisition when integrated into classroom instruction.